Local injection of CCL19-expressing mesenchymal stem cells augments the therapeutic efficacy of anti-PD-L1 antibody by promoting infiltration of immune cells - Mitsuo Oshimura; Yuichi Iida; Rintaro Yoshikawa; Akihiko Murata; Hitoshi Kotani; Yasuhiro Kazuki; Yumi Matsuzaki; Mamoru Harada (Journal for ImmunoTherapy of Cancer)
Background Mesenchymal stem/stromal cells (MSC) accumulate and reside in tumor sites.Methods Taking advantage of this feature in anticancer therapy, immortalized murine MSC (iMSC) were genetically altered to produce chemokine (C-C motif) ligand 19 (iMSC/CCL19), which attracts dendritic cells (DC) and T lymphocytes. Thereafter, iMSC/CCL19 were examined for their therapeutic efficacy using a syngeneic CT26 colon carcinoma cell line.Results Co-injection of iMSC/CCL19 into mice significantly suppressed the in vivo growth of CT26 cells compared with that of CCL19-expressing immortalized fibroblasts (iFib/CCL19). This anticancer effect was not observed when injected in CT26-bearing nude mice. Co-injected iMSC/CCL19 survived longer than iFib/CCL19 in the tumor sites. In a therapeutic model, local injection of iMSC/CCL19 suppressed the tumor growth, and increased IFN (interferon)-γ+ CD8+ T cells and CCR7+ DC infiltration in tumor site was observed when treated with iMSC/CCL19, but not with iMSC. This antitumor effect was completely negated by depletion of CD4+ cells and partially negated by depletion of CD8+ cells. Furthermore, the antitumor effects induced by local injection of iMSC/CCL19 were augmented by additional therapy with anti-programmed death (PD)-ligand 1 (PD-L1) antibody, but not with anti-PD-1 antibody. This combination therapy cured most of the tumors in CT26-bearing mice.Conclusion These results suggest that local therapy with iMSC/CCL19 can suppress tumor growth via effective recruitment of CCR7+ DC into tumor sites and increase IFN-γ+ CD8+ T cells, and that combination with anti-PD-L1 antibody therapy can be a powerful anticancer therapy.